SERVICE OF PEOPLE WITH PSYCHIATRIC PROBLEMS (ODMK) AT THE PASAR BARU HEALTH CENTER AND PABUARAN TUMPENG HEALTH CENTER IN TANGERANG CITY IN 2022: A COMPARATIVE STUDY - Firdaus, Mentari Kirana; Basabih, Masyitoh (UI Scholars Hub, 2022)
Mental health is one of the global health issues with cases that continue to increase every year. In 2019, psychiatric problems were the second leading cause of disability worldwide with a total of 970 million cases. This research is a comparative study that aims to determine the difference between ODMK services at Pasar Baru Health Center and Pabuaran Tumpeng Health Center. This research uses a qualitative approach with a case study method, data collection is done through in-depth interviews and document review. The variables analyzed include input, process, and output. The results of the study found that in the input variable, health human resources at Pabuaran Tumpeng Health Center had a higher workload than health human resources at Pasar Baru Health Center. In the process variable, Pasar Baru Health Center is able to carry out innovative activities to improve ODMK services during the pandemic. In the output variable, it was found that the quality of service at the Pasar Baru Health Center was better than the Pabuaran Tumpeng Health Center, besides that the coverage of ODMK services at the Pasar Baru Health Center in 2021 reached 128% while at the Pabuaran Tumpeng Health Center it only reached 77%. This study concludes that the health center that have adequate human resources and able to carry out services according to the existing situation, can produce higher quality services and achieve service coverage targets.